PDGFRα signaling regulates cartilage and fibrous tissue differentiation during synovial joint development - John P. Woods; Alex Rackley; Hae Ryong Kwon; Lorin E. Olson (Nature Communications)
Abstract Synovial joints develop from mesenchymal structures called interzones, with progenitor cells differentiating into specialized cartilaginous and fibrous tissues of the joint. Platelet-derived growth factor receptor-α (PDGFRα) is a tyrosine kinase expressed by cells of the limb bud, but its role in limb development is unknown. To investigate PDGFRα function, we generated mice expressing mutant PDGFRα with a point mutation (D842V) that increases receptor signaling. Mutant hindlimbs are immobile with knee joints fused by cartilage and lacking ligaments and menisci. The interzone marker Gdf5 is initially expressed at E12.5 but is downregulated thereafter, suggesting a defect in interzone maintenance. Omics analysis of the joint tissues identifies ectopic cartilage matrix expressing genes for cartilage and fibrotic tissue. Thus, elevated PDGFRα signaling corrupts joint development by downregulating Gdf5 and redirecting interzone progenitors into a fibrocartilage fate. This suggests that tight regulation of tyrosine kinase activity is necessary for the development of the mouse knee joint.